2018
DOI: 10.1186/s12906-018-2153-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of cytotoxic and antioxidative activities of Ardisia crispa against breast cancer cell lines, MCF-7 and MDA-MB-231

Abstract: BackgroundArdisia crispa Thunb. D.C is used mostly in some parts of the Asian region by traditional practitioners to treat certain diseases associated with oxidative stress and inflammation including cancer and rheumatism. In Malaysia, it is popularly known as ‘Mata Ayam’ and local traditional practitioners believed that the root of the plant is therapeutically beneficial.MethodsThe cytotoxic effect of hydromethanolic extract of A. crispa and its solvents partitions (ethyl acetate and aqueous extracts) against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 40 publications
2
40
0
2
Order By: Relevance
“…This means that polar solvent was used since methanol and water were classified as polar solvent. Hydromethanolic extract (mixture of methanol and water) has greater efficiency in pulling out (extract) phytochemical compound in plant compared to pure solvent (without mixture) [20,26,27]. Interestingly, in this study, it was found that both antibacterial and cytotoxic activities of this plant are considered weak.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This means that polar solvent was used since methanol and water were classified as polar solvent. Hydromethanolic extract (mixture of methanol and water) has greater efficiency in pulling out (extract) phytochemical compound in plant compared to pure solvent (without mixture) [20,26,27]. Interestingly, in this study, it was found that both antibacterial and cytotoxic activities of this plant are considered weak.…”
Section: Discussionmentioning
confidence: 82%
“…[19] and Nordin et al . [20]. Cytotoxicity activity of S. polyanthum extract was prepared with concentrations ranging from 15.63 µg/mL to 1000 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracting ratio of total flavonoids from T. jasminoides by an ultrasonic wave cooperated method was 3.22% [28], which was a bit higher than that achieved by our ethanol soaking extraction. It is commonly considered that medicinal plants with high amounts of phenols and flavonoids have potential antioxidant actions [29,30], which prompted us to evaluate the antioxidant activity.…”
Section: Total Phenolic and Flavonoid Contentmentioning
confidence: 99%
“…About 500 species of evergreen trees and shrubs are commenced throughout the tropical and sub-tropical regions of the universe [8]. Besides, A. compressa possesses significant hypoglycemic effects in Type 2 diabetic rats, and antioxidant activity and A. crispa showed in vitro cytotoxic activity and antioxidative actions against breast cancer cell lines [9]. Barks and leaves of A. colorata were extracted with ethanol having antimicrobial activities [10].…”
Section: Introductionmentioning
confidence: 99%